Cortical network characteristics in post-stroke anxiety: an fNIRS-based study - Qian, Xue; Wang, Qinglei; Wang, Jie; Yang, Ling; Geng, Ayan; Xu, Wenjie; Dong, Gengjuan; Lu, Tongbo; Guo, Chuan (Frontiers in Neuroscience, 2026)
ObjectiveTo examine prefrontal hemodynamic changes in patients with post-stroke anxiety (PSA), both at rest and during cognitive task engagement, with the aim of elucidating the underlying neural mechanisms of PSA and identifying potential neural correlates for clinical application.MethodsFifty patients with PSA and 45 post-stroke patients without anxiety symptoms were recruited. PSA was diagnosed using the Hamilton Anxiety Rating Scale (HAMA ≥ 7), and comorbid depression was screened using the 17-item Hamilton Depression Rating Scale (HAMD-17 ≥ 8). Patients with significant cognitive impairment were excluded. Functional near-infrared spectroscopy (fNIRS) was used to measure resting-state functional connectivity in the frontopolar cortex (FPC) and dorsolateral prefrontal cortex (DLPFC), as well as task-evoked activation during the verbal fluency task (VFT). Demographic and clinical characteristics showed no significant differences between groups except for stroke type. Between-group comparisons were conducted to identify PSA-related differences in prefrontal network characteristics. Subgroup analyses were performed to explore the influence of comorbid depression on neural alterations.ResultsThere were no significant differences between the PSA and non-PSA groups in demographic or clinical characteristics, including age, sex, and disease duration (P > 0.05). Compared to the non-PSA group, patients with PSA exhibited significantly reduced activation in the bilateral FPC during the VFT (P < 0.05). Within the PSA group, those with comorbid depression showed further reductions in activation in the bilateral FPC and the left DLPFC (P < 0.05). No significant differences in resting-state functional connectivity were observed between groups (P > 0.05).ConclusionReduced activation in the bilateral FPC may represent a key neural substrate associated with post-stroke anxiety. In addition, altered activation patterns in the bilateral FPC and left DLPFC may reflect neural correlates related to depressive symptoms in patients with PSA, providing candidate targets for future mechanistic and clinical studies.